2020
DOI: 10.3390/cells9030707
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Advances of Stem Cell-Derived Extracellular Vesicles in Regenerative Medicine

Abstract: Extracellular vesicles (EVs), which are the main paracrine components of stem cells, mimic the regenerative capacity of these cells. Stem cell-derived EVs (SC-EVs) have been used for the treatment of various forms of tissue injury in preclinical trials through maintenance of their stemness, induction of regenerative phenotypes, apoptosis inhibition, and immune regulation. The efficiency of SC-EVs may be enhanced by selecting the appropriate EV-producing cells and cell phenotypes, optimizing cell culture condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 112 publications
0
49
0
Order By: Relevance
“…Currently efforts are underway to develop lipid nanoparticles that can be delivered to target cells following intravenous (IV) injection (hepatocytes) allowing the efficient transfer of miRNA [32]. As research on extracellular vesicles advances, the paracrine and regenerative effects of stem cells mediated via EVs have been demonstrated [33]. Because EVs are natural vesicles they are considered to be safer and more effective than artificial alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Currently efforts are underway to develop lipid nanoparticles that can be delivered to target cells following intravenous (IV) injection (hepatocytes) allowing the efficient transfer of miRNA [32]. As research on extracellular vesicles advances, the paracrine and regenerative effects of stem cells mediated via EVs have been demonstrated [33]. Because EVs are natural vesicles they are considered to be safer and more effective than artificial alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, EVs can promote myocardial regeneration and restore cardiac Most of the literature concerning EVs released by MSCs is isolated from different tissues. That is why we barely mention the topic and for more in depth information we refer to some recent reviews [159,160].…”
Section: Extracellular Vesicles-based Regenerative Medicinementioning
confidence: 99%
“…As described above, more and more in vitro and preclinical studies have demonstrated that stem cells exert their regenerative potential via paracrine mechanisms, which include EV release. Due to their lower immunogenicity, easier handling, and having no risk of tumor formation, researchers recently focused on their potential as possible alternatives to stem cells [159,[204][205][206], studying experimental model diseases treated with MSC-EVs. To date, a total of eight clinical trials on the application of EVs for disease treatment were identified [160].…”
Section: Induced Pluripotent Stem Cell Derived Evs In Regenerative Mementioning
confidence: 99%
“…Proteins present in the extracellular BM-MSC vesicles also include signaling molecules such as mitogen-activated protein kinase (MAPK1), an enzyme expressed by the MAPK1 gene, cell adhesion mediators such as fibronectin, and surface receptors such as the PDGF receptor. MSC-derived extracellular vesicles also express regulatory molecules such as transforming GF beta (TGF-β), galectin-1, and programmed death-ligand1 (PD-L1), mediators involved in the processes of differentiation, proliferation, and cell apoptosis [ 213 , 214 ].…”
Section: Cell-mediated Biomolecular and Antioxidative Mechanisms Imentioning
confidence: 99%